Proliferating Textual Possibilities: Toward Pedagogies of Critical-Creative Tinkering. - Koupf, Danielle (Composition Forum)
Tinkering is a longstanding material practice that has gained popularity in recent years as a learning strategy at numerous schools, camps, and makerspaces. This article seeks to establish in composition pedagogy tinkering's playful, exploratory ethos by introducing a practice called critical-creative tinkering. In critical-creative tinkering, a writer dwells inside a source text by reading and rewriting it, generating an alternative text. Building on the itinerant status of traditional tinkers, this article promotes critical-creative tinkering as a pedagogy that moves or travels across the curriculum. Toward that end, it presents tinkering assignments and student responses to them from two different writing-intensive courses: an introductory literature course and a professional writing course.